Dual role of Chlorella vulgaris in wastewater treatment for biodiesel production: Growth optimization and nutrients removal study - Khoo, C.G. (Japan Institute of Energy, 2017)
The environmental footprint for microalgae based biofuel can be reduced by coupling the microalgae cultivation with wastewater treatment. In the present study, the nutrients source for microalga Chlorella vulgaris was replaced by municipal wastewater from wastewater treatment plant located at USM Engineering Campus, Penang. All cultivation experiments were conducted in 5 L photobioreactors (PBRs) under indoor condition with illumination from artificial lights and compressed-air aeration. The growth performances of microalga C. vulgaris and nutrients uptake from wastewater were monitored throughout a 13-day cultivation period. The nutrients removal efficiency (NRE) for total nitrogen (TN) and total phosphorus (TP) by microalgae are 72.1 wt and 89.7 wt, respectively under the optimum cultivation conditions. Subsequently, microalgae biomass was collected by flocculation method, followed by extraction of lipid and transesterified to biodiesel. It was found that the biomass collected under optimum cultivation conditions achieved a maximum biomass dry weight density (N) of 0.76 g/L (or an equivalent biomass daily productivity, P of 58.6 mg/(L·d)). © 2017, Japan Institute of Energy. All rights reserved.